A rare case of osteomyelitis of the clavicle in a child due to Group A streptococcal infection. Issue 4 (11th April 2019) - Ahmed, Molla Imaduddin; Nadeem, Muhammad; Bandi, Srini
Abstract : Acute osteomyelitis of the clavicle is rare in the paediatric age group. We treated a 5-year-old boy who presented initially with fever and left shoulder pain, and subsequently developed swelling in the region of the left clavicle. Group A Streptococcus (GAS) was isolated in blood culture. MRI of the clavicle showed osteomyelitis of the medial clavicle. The child had incision and drainage of his clavicular collection. The child received intravenous benzylpenicillin and oral cephalexin in the initial presentation; he was treated with 2 weeks of intravenous ceftriaxone and 4 weeks of oral penicillin thereafter with the resolution of his symptoms. There are no previous case reports of osteomyelitis of the clavicle in children caused by GAS. This case highlights the importance of identifying the microbial aetiology in these children to ensure early initiation of treatment with appropriate antibiotics.